Comparison of herbal products with antifungal drugs in cure of oral candidiasis: A systematic review - Faezeh Khozeimeh; Negar Ghadiri; Behzad Zolfaghari; Bahareh Tahani (Dental Research Journal, 2025)
Background: Oral candidiasis is one of the most common fungal infections affecting the oral mucosa. It is usually managed by taking antifungal medication that might result in side effects such as toxicity and drug resistance. Therefore, consumption of herbal medicine with antifungal activity and fewer side effects has become popular. This study is a systematic review to investigate the improvement and reduction of oral candidiasis symptoms by herbal compounds compared to conventional antifungal drugs. Materials and Methods: PubMed, Scopus, Web of Science, Cochrane, and Magiran databases were searched from 1995 to 2021 based on the keywords of the question formula – oral candidiasis (P), herbal compounds (I), antifungal drugs (C), and improvement of clinical symptoms and laboratory tests (O) – to find related randomized controlled trials (RCTs) in English and Persian languages. Related articles were extracted based on inclusion and exclusion criteria and critically appraised using the modified-CONSORT checklist. The risk of bias was also assessed using the Cochrane tool. Results: After removing duplicates and checking the title and abstract of the articles, 98 articles from 1995 to November 2021 of 715 were reviewed. 83 RCTs were excluded due to non-relevancy and 15 remained for critical appraisal, of which 5 articles were rejected. Finally, 10 articles were included in the systematic review. Based on the risk of bias assessment, one article had low risk, 6 articles had unclear risk, and 3 articles had a high risk of bias. Herbal compounds were applied in the form of gel in 3 articles, in the form of ointment and mouthwash in 1 and 6 articles, respectively. In terms of clinical improvement and laboratory findings, herbal compound mouthwashes and ointment did not have a significant difference from conventional antifungal drugs, but the articles related to compound gels reported variable effects (better, similar, and weaker). Furthermore, herbal compounds generally had more patient satisfaction than antifungal drugs. Conclusion: It seems that herbal compounds have clinical applications in the treatment of oral candidiasis and gained more patients’ satisfaction. To achieve more valid results, it is suggested to conduct more RCTs with a low risk of bias.